Triple-sensitivity high-spatial-resolution X-ray computed tomography using a cadmium-telluride detector and its beam-hardening effect. (May 2020) - Yoshida, Sohei; Sato, Eiichi; Oda, Yasuyuki; Yoshioka, Kunihiro; Moriyama, Hodaka; Watanabe, Manabu
Abstract: To observe blood vessels at high contrasts, we constructed a first-generation triple-sensitivity X-ray computed tomography (TS-CT) scanner using a cadmium-telluride (CdTe) detector and a triple-amplifying system. X-ray photons are absorbed by the CdTe crystal, and the electric charges produced by photons are converted into voltages using a current-to-voltage (I–V) amplifier, and the I–V output is amplified by a voltage-to-voltage (V–V) amplifier. The V–V output 1 is sent to a dual V–V amplifier through a 5.0-m-length coaxial cable and amplified to two-different outputs of 2 and 3. The three outputs 1–3 are sent to a personal computer through an analog-to-digital converter to reconstruct three tomograms simultaneously. In the TS-CT, the scattering photons from the object are extremely reduced using a 0.5-mm-diameter lead pinhole behind the object. The translation and rotation steps were 0.1 mm and 0.5°, respectively, and the spatial resolutions were 0.25 × 0.25 mm 2 . The scanning time was 19.6 min, and blood vessels were visible using gadolinium contrast media. In particular, the effective photon energy increased with increasing amplification factor of the amplifier caused by beam hardening of the object. Highlights: Entire X-ray photons are detected using high-sensitivity CdTe module. Triple-sensitivity CT was performed by module and dual amplifier. Triple-energy CT was accomplished using beam hardening by object. Effective energy increases with increasing amplification factor. Strong contrast variations of Gd media were observed with changes in factor.